A2_5 Go Long, Earthlings! - Perks, Megan; Stylianou, Natalia; Filip, Tom; McMullan, Mac (Physics Special Topics, 2021)
This article investigates whether an American football shaped planet such as KOI 1843.03 could exist in our Solar System and whether or not it could be potentially habitable. It was found that the smallest orbital radius at which such an Earth-mass planet could occur is a = 8.26x10^8 m, if it is made of pure iron, but that the effective surface temperature (assuming an Earth-like albedo value of α = 0.3) would be T_e = 3428 K (or 3155^o C) which far exceeds the habitable limit.